Analisis Usahatani Semangka Berbiji Di Kelurahan Ringinanom Kecamatan Nganjuk Kabupaten Nganjuk - Fitri Krismiratsih; Suwinda Fibriani; Nisa Budi Arifiana (Politeknik Kampar, 2023)
The purpose of this research is to determine the income from watermelon farming as seen from production in the Ringinanom sub-district, Nganjuk District, Nganjuk Regency. The research method used in this research is a quantitative method which is strengthened by descriptive qualitative methods by conducting R/C ratio analysis. Based on the results of the research described previously, the income from watermelon farming in Ringinanom Village, Nganjuk District, Nganjuk Regency was Rp. 2,132,000,. The results of the R/C Ratio analysis are 1.34, which means the farming business is worth pursuing. The BEP Product value is 480 Kg, and the BEP Price is IDR. 3,742